THE ROLE OF POTASSIUM AND CALSIUM IN IMPROVING THE QUALITY AND SHELF LIFE OF TOMATO (Lycopersicum esculentum var. servo) - Wicaksana, Puguh Catur; Wijaya, Ketut Anom; Soeparjono, Sigit (El-Hayah : Jurnal Biologi, 2019)
Tomato has the characteristics natural to damage. Damage fruits are caused by destitute of fruit quality and sensory attributes. The loss of tomato production on harvest in developing countries reached 50% due to the long duration of tomato distribution. Servo varieties of tomatoes are in demand by farmers because of their genetic advantages, high productivity, and abundant fruit weights. The shortage of servo varieties of tomatoes is the short shelf life of fruit, which is seven days after harvest. Short shelf life is influenced by fruit thickness and fruit hardness. In improving the quality and shelf life of tomatoes, potassium (K) nutrition plays a role in photosynthetic translocation, strengthens the cell wall, and involved in the lignification process of sclerenchyma tissue. Tomatoes, as climacteric fruits have a high respiration rate influenced by ethylene. Ethylene production can be inhibited by calcium chloride (CaCl2) application by strengthening the cell wall mechanism, cross-link with pectin, and increase the cell wall regeneration can change the texture of the fruit become harder, and it reduces sensitivity to physiological damage. Based on the treatment of this research, the quality and shelf life of servo varieties of tomato is increased.